Associations of marital status with diabetes, hypertension, cardiovascular disease and all-cause mortality: A long term follow-up study - Ramezankhani, Azra (PLoS One, 2019)
BACKGROUND: To investigate the associations of marital status with major clinical outcomes including type 2 diabetes (T2D), hypertension, cardiovascular disease (CVD) and all-cause mortality. METHODS: The study cohort (1999–2014) included 9,737 (45% male) Iranian adults with a mean age of 47.6 years. Marital status was defined as married versus never married, divorced and widowed. The relationship between marital status and the four above mentioned outcomes were investigated using Cox regression models adjusted for the main confounders, specific to each outcome. RESULTS: After more than 12 years of follow-up, 1,889 (883 men) individuals developed hypertension, 1,038 (468 men) T2D, 1015 (597 men) CVD and 668 (409 men) all-cause mortality. Compared with married, being never married in men was associated with higher risk of hypertension [hazard ratio (HR): 1.55; 95% confidence interval (CI), 1.11–2.16] and all-cause mortality (2.17; 0.95–5.00; p-value = 0.066) after adjusting for confounders. Among women, compared with married status, widowed status was associated with a lower risk of T2D (0.74; 0.56–0.97) in the confounders adjusted model. Moreover, never married women had a lower risk of hypertension (0.58; 0.37–0.90) compared to married ones in the age adjusted model, a finding that did not achieve significance, after further adjustment for confounders. CONCLUSION: We found that the relationship between marital status and health outcomes varied by gender. Being never married was an important risk factor for hypertension and tended to be a significant risk factor for mortality in men. However, among women, being widowed was associated with a lower risk of T2D.